The world's worst children 1 - Walliams, David; Ross, Tony (London harpercollins children's book, 2023)
Are you ready to meet the world's worst children? Five beastly boys and five gruesome girls! Like Sofia Sofa - a TV super-fan so stuck to the sofa that she's turning into one! Or Dribbling Drew - a boy whose drool gets him into trouble on a school trip! And not forgetting Blubbering Bertha - a girl who bawls and tells terrible tales!
From the number one bestselling author
Science fiction
Keywords: Children's -- Teenage fiction & true stories; Children's -- Teenage personal & social issues; English fictions